2008
DOI: 10.1038/cgt.2008.78
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Wnt2 and β-catenin by siRNA suppresses malignant glioma cell growth

Abstract: Increasing evidence suggests that aberrant activation of Wnt signaling is involved in tumor development and progression. Our earlier study on gene expression profile in human gliomas by microarray found that some members of Wnt family were overexpressed. To further investigate the involvement of Wnt signaling in gliomas, the expression of core components of Wnt signaling cascade in 45 astrocytic glioma specimens with different tumor grades was examined by reverse transcription-PCR and immunohistochemistry. Wnt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
177
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(191 citation statements)
references
References 37 publications
8
177
6
Order By: Relevance
“…Although the expression of Wnt/β-catenin signaling pathway members in glioma has been demonstrated previously (15,(18)(19)(20), there is a lack of studies that have systematically investigated the expression of Wnt signaling. In order to comprehensively characterize the expression of Wnt signaling in glioma tissues, the R2: Genomics Analysis and Visualization Platform database was interrogated, which revealed that, in patients with glioma, the median mRNA expression levels of Wnt2b, Wnt5a, FZD1-7 were increased compared with other Wnt pathway members (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the expression of Wnt/β-catenin signaling pathway members in glioma has been demonstrated previously (15,(18)(19)(20), there is a lack of studies that have systematically investigated the expression of Wnt signaling. In order to comprehensively characterize the expression of Wnt signaling in glioma tissues, the R2: Genomics Analysis and Visualization Platform database was interrogated, which revealed that, in patients with glioma, the median mRNA expression levels of Wnt2b, Wnt5a, FZD1-7 were increased compared with other Wnt pathway members (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the mRNA expression levels of Wnt ligands, receptors, β-catenin destruction complex and its target genes cyclin D1 and AXIN2 were determined using qPCR. Based on previous studies, which detected the Wnt ligands in glioma cells and tissues (15,18), eight members of the Wnt family (Wnt2b, 3, 3a, 5a, 5b, 7b, 9b and 11) were selected for further investigation. As presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro and in vivo experiments, using siRNA for Wnt2 and β-catenin, have demonstrated inhibition of cell proliferation and invasion as well as inhibition of tumor development. Furthermore, suppression of Wnt2 and β-catenin is associated with reduced PI3K/Akt expression that is associated with an interaction between Wnt/β-catenin and PI3K/Akt signal cascades [59]. Expression of CD133 and Wnt-1 is elevated in the stem cells isolated from the glioblastomas.…”
Section: Therapeutic Approaches To the Target Impacts On The Cancer Smentioning
confidence: 94%
“…This complex regulates transcription of multiple genes involved in cellular proliferation, differentiation, survival and apoptosis, including Fra-1, c-myc and Cyclin D. In the past, our group has demonstrated that Wnt/β-catenin/TCF signaling was significantly dysregulated in gliomas and down-regulated β-catenin/ TCF signaling which can inhibit cell proliferation and invasive ability, induced apoptotic cell death (23). Furthermore, we clarified that down-regulation of β-catenin/TCF signaling inhibited several members of the EGFR pathway in human glioma cells (24).…”
Section: Discussionmentioning
confidence: 99%